The Native and the Refugee - Peterson, Matt; Rasamny, Malek (The Native and the Refugee)
A multi-media project profiling the spaces of the Indian reservation and Palestinian refugee camp: spaces of exception whose position in the struggle for native and Palestinian autonomy are essential. The Native and the Refugee will culminate in a feature-length documentary film.
Keywords: afrique; amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; camps de réfugiés; cours; discipline; documentaire; gaza; justice sociale; militance; palestine; pol5480; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences